2009
DOI: 10.1111/j.1601-5037.2009.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

How clean is the toothbrush that cleans your tooth?

Abstract: Until recently, little attention has been directed towards the role the toothbrush may play in human health, even though a report of toothbrush as a significant factor in the infection appeared in 1920. It is common knowledge that the human mouth harbours a wide variety of microorganisms, some of which, at any given time, can be assumed to be potential pathogens. This was not known when toothbrushes were originally designed, yet the common toothbrush has been used in basically the same form for about 200 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 6 publications
0
42
0
9
Order By: Relevance
“…In general, contamination can arise when toothbrushes and toothpastes are shared, or when toothbrushes are stored with the toothbrushes of other individuals. 2,20 In this study, the surveyed dentists mostly stored their toothbrushes in closed places in a toothbrush holder shared with other individuals, and they shared their toothpaste with other individuals. Compared to male dentists, significantly more female dentists indicated that they thought contact between toothbrushes was an important issue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, contamination can arise when toothbrushes and toothpastes are shared, or when toothbrushes are stored with the toothbrushes of other individuals. 2,20 In this study, the surveyed dentists mostly stored their toothbrushes in closed places in a toothbrush holder shared with other individuals, and they shared their toothpaste with other individuals. Compared to male dentists, significantly more female dentists indicated that they thought contact between toothbrushes was an important issue.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a toothbrush cap has also been reported to increase bacterial survival on toothbrushes. 2,5,18 Nascimento et al 19 investigated the effectiveness of three antimicrobial mouth rinses for toothbrush disinfection under in vivo conditions. The participants of that study stored their toothbrushes in closed containers to avoid external contamination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations